(untitled) (AYUSHDHARA, 2016)
Ayurveda is a science which has many basic principles which are fruitful even today. One of the basic principle for diagnosis and treatment of disease is based on Swaroop, Guna and Karma of Dosha, Dhatu, Mala. Guna Vichara is useful in understanding the pathogenesis of Roga (disease) by Vikalpa Samprapti and pharmaceutical action in Aushdha (drug). Guna resides in Dravya by Samvaya Sambandha (inseparable relation). Even Dosha, Panchmahabhuta which are essential in basic understanding of disease are described in terms of Guna. Basically Guna present in Dravya acts upon the body hence provide the same effect as per Dravya. Hence it is very essential to study Guna to understand pathophysiology and to cease and treat disease. Amlapitta is a disease caused by Drava and Ushna Guna of Pitta Dosha. If Drava Guna of Pitta is more aggravated comparative to Ushna guna than Ruksh ushna dravya should be preferred in line of treatment similarly if Ushna guna is more aggravated than Sheeta guna pradhan aushadh should be preferred. Thus this paper depicts the value of Guna with respect to treatment of disease concerned on Amlapitta only.